MANAGEMENT OF GRADE II HYPERTENSION WITH HEART FAILURE - Indah Dwi Pratiwi (Fakultas Kedokteran Universitas Lampung, 2014)
Hypertension is one of the most prevalent diseases in the family medicine’s services, and if it is not properly managed it can causefatal complication to death, due to heart attacks, strokes, and even kidney failure. Primary data were obtained through anamnesis, physical examination, and home visit follow-up. Secondary data were obtained from patient’s medical record. Patient, Mr. R, 83 years old with grade II hypertension and heart failure NYHA II. Risk factors for this patient are elderly, hypertension, smoking, and poor lifestyle. Physical examination obtained 160/80 mmHg, JVP 5 + 3 cm H2O, an enlarged heart with murmur sound. The patient was given ACE inhibitor, Betablocker, and Diuretics. Education about the disease and the importance of blood pressure control and prevention of complications also had been given. Within 21 days, showed a decrease in blood pressure fotm 160/80 mmHg to 130/80 mmHg. [J Agromed Unila 2014; 1(2):88-91]Keywords: heart failure, hypertension